The Ethics of Deuteronomy: An Exegetical and Theological Study - Millar, J. Gary (Tyndale bulletin, 1995)
A dissertation exploring the ethics of Deuteronomy from exegetical and theological perspectives; it is affirmed that its ethics are based on the response to Yahweh’s gracious initiatives demanded of Israel.